Estudio y eleccion de progenitores en cultivares de tomate para consumo fresco - Castillo Muñoz, A.=700 1 Abreus Sosa, O.; Mujica Sanchez, R.; Hernandez leon, A.; Ravelo Gutierrez, A.
(En, Es)
ilus., 9 ref.
Keywords: TOMATE; VARIEDADES; PROGENIE; FRUTAS; CUBA